Machine Learning Applied to the Measurement of Quality in Health Services in Mexico: The Case of the Social Protection in Health System - Rodriguez-Aguilar, R. (Springer Verlag, 2019)
To propose a satisfaction indicator of users of health services affiliated to the Social Protection System in Health (SPSS). Identify the effect of the main factors that are directly related to the satisfaction level and perception of quality of health services. A machine-learning model based on Logistic Models and Principal Components was developed to estimate a satisfaction index. The survey data collected for the âSPSS 2014 Userâs Satisfaction Studyâ was used, considering a sample of 28,290 users. The proposed model shows, in general, the positive perception of quality of health services (national average 0.0756). There are factors statistically significant that influence these results, the good perception of infrastructure (OR:2.12; CI 95:1.9â2.36); the gratuity of the service provided (OR:1.98; CI 95: 1.42â2.76); and full medicines supply (OR:1.81; CI 95:1.91â2.36). The proposed index can be used as an indicator for improving health care quality of the population covered by the SPSS. Â© 2019, Springer Nature Switzerland AG.